Gaze behavior of gymnastics judges: where do experienced judges and gymnasts look while judging? - Pizzera, Alexandra; Möller, Carsten; Plessner, Henning (Research quarterly for exercise and sport, 2018)
Gymnastics judges and former gymnasts have been shown to be quite accurate in detecting errors and accurately judging performance. Purpose: The purpose of the current study was to examine if this superior judging performance is reflected in judges’ gaze behavior. Method: Thirty-five judges were asked to judge 21 gymnasts who performed a skill on the vault in a video-based test. Classifying 1 sample on 2 different criteria, judging performance and gaze behavior were compared between judges with a higher license level and judges with a lower license level and between judges who were able to perform the skill (specific motor experience [SME]) and those who were not.